Pengaruh Massage dengan Virgin Coconut Oil (VCO) untuk Mencegah Luka Dekubitus pada Pasien Stroke Hemoragik - Anita Shinta Kusuma; Agustian, Billy Cahya (STIKES Ngesti Waluyo, 2023)
Stroke is a disease caused by the narrowing of the blood vessels in the brain so that the flow of blood and oxygen to the brain is hampered and even stopped. Based on Basic Health Research in 2018, it states that in Indonesia the prevalence of stroke based on diagnosis in the population of 15 years of age reaches 10.9%. Stroke patients who experience total bed rest have a high risk of experiencing pressure sores. The purpose of this paper is to determine the effectiveness of massage with Virgin Coconut Oil (VCO) to prevent the occurrence of pressure sores in hemorrhagic stroke patients. This study used the method of Literature Review. The literature search was conducted through Google Scholar, Garuda, and ProQuest databases. There were 32 articles found which were then further checked for suitability and obtained 10 articles reviewed in this study. The result of the articles described the action of massage with VCO effect in preventing the occurrence of pressure sores. Massage procedures with VCO can be applied in stroke patients because it is proven to be effective in preventing the occurrence of pressure sores.